2017
DOI: 10.1186/s13568-017-0506-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbial consortia and chemical changes in spontaneous maize bran fermentation

Abstract: Sustainable exploitation of agro-industrial by-products has attracted great interest in cereal bran valorization. In this research, a polyphasic approach has been carried out to characterize maize bran at microbiological and chemical level during a sourdough like fermentation process, in order to enhance its technological and nutritional properties. Autochthonous microbiota was isolated at different refreshment steps and subjected to identification and molecular characterization. Fermentation was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…acidilactici in the final phases dominated the microbial community. These species have been previously reported in sourdoughs made from a range of cereals, including spelt (Van der Meulen et al 2007;Coda et al 2010;Manini et al 2014;Decimo et al 2017). However, our findings highlight the dominance of Ped.…”
Section: Microbial Population Dynamicssupporting
confidence: 54%
See 2 more Smart Citations
“…acidilactici in the final phases dominated the microbial community. These species have been previously reported in sourdoughs made from a range of cereals, including spelt (Van der Meulen et al 2007;Coda et al 2010;Manini et al 2014;Decimo et al 2017). However, our findings highlight the dominance of Ped.…”
Section: Microbial Population Dynamicssupporting
confidence: 54%
“…Total bacterial DNA was extracted from 100 µl of an overnight culture, using the Microlysis kit (Labogen, Rho, Italy) following the manufacturer’s instructions. For yeasts, DNA extraction was performed in a PRECELLYS®24‐DUAL lyser/homogeniser (Bertin‐Technologies, Saint Quentin en Yvelines, France), as previously described (Decimo et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast species diversity in sourdough has been well described in Italy, Belgium, and France (Figures 2 and 3, Table S1). We analysed the data obtained for 97 wheat sourdoughs (including possibly also other cereals) described individually (Almeida & Pais, 1996;Corsetti et al, 2001;Decimo, Quattrini, Ricci, Fortina, & Express, 2017;Desiye & Abegaz, 2013;Foschino, Gallina, Andrighetto, Rossetti, & Galli, 2004;Gabriel, Lefebvre, Vayssier, & Faucher, 1999;Garofalo, Silvestri, Aquilanti, & Clementi, 2008;Infantes & Schmidt, 1992;Lacumin et al, 2009;Lattanzi et al, 2013;Lhomme et al, 2015;Lhomme et al, 2016;Mäntynen et al, 1999;Minervini et al, 2015;Obiri-Danso, 1994;Osimani et al, 2009;Pulvirenti, Caggia, Restuccia, Gullo, & Giudici, 2001;Saeed Anjum, Zahoor, Nawaz, & Sajjad-Ur-Rehman, 2009;Salovaara & Savolainen, 1984;Scheirlinck et al, 2007;Spicher & Schröder, 1978;Succi et al 2003;Vrancken et al, 2010;Valmorri, Tofalo, Settanni, Corsetti, & Suzzi, 2010;Zhang et al, 2015;Zhang et al, 2011). S. cerevisiae was found to be present, but not necessarily dominant, in almost 80% of the sourdoughs ( Figure 3).…”
Section: The Sourdough Microbial Communitymentioning
confidence: 99%
“…Successively, many authors have reported positive results in the reduction of PI using lactic acid bacteria and yeasts, improving the bioavailability of minerals in fermented maize [135,136]. The reduction of phytic acid by the natural microbiota has also been reported during the fermentation of maize bran by Decimo et al [137]; in this case a reduction of 50% at the end of the sourdough-like fermentation process (corresponding to the twelfth refreshment), was reported.…”
Section: Reduction Of Phytatesmentioning
confidence: 87%